2022
DOI: 10.15252/embr.202153608
|View full text |Cite
|
Sign up to set email alerts
|

XIAP promotes melanoma growth by inducing tumour neutrophil infiltration

Abstract: Elevated expression of the X‐linked inhibitor of apoptosis protein (XIAP) has been frequently reported in malignant melanoma suggesting that XIAP renders apoptosis resistance and thereby supports melanoma progression. Independent of its anti‐apoptotic function, XIAP mediates cellular inflammatory signalling and promotes immunity against bacterial infection. The pro‐inflammatory function of XIAP has not yet been considered in cancer. By providing detailed in vitro analyses, utilising two independent mouse melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
0
13
1
Order By: Relevance
“…Bax, one of the Bcl-2 family members, promotes apoptosis by damaging mitochondrial membrane integrity, whereas Bcl-2 inhibits apoptosis by maintaining the integrity of the mitochondrial membrane [ 34 ]. The X-linked inhibitor of apoptosis protein has also been implicated in mitochondrial apoptosis [ 35 ]. It inhibits apoptosis mainly by interacting directly with caspases to inhibit them.…”
Section: Discussionmentioning
confidence: 99%
“…Bax, one of the Bcl-2 family members, promotes apoptosis by damaging mitochondrial membrane integrity, whereas Bcl-2 inhibits apoptosis by maintaining the integrity of the mitochondrial membrane [ 34 ]. The X-linked inhibitor of apoptosis protein has also been implicated in mitochondrial apoptosis [ 35 ]. It inhibits apoptosis mainly by interacting directly with caspases to inhibit them.…”
Section: Discussionmentioning
confidence: 99%
“…54 Abnormal expression of XIAP is directly associated with cancer, autoimmune diseases and neurodegenerative diseases. 55,56 However, the role of XIAP in psoriasis has not been studied. In this study, RNA-seq analysis, qRT-PCR and western blot results showed that XIAP was highly expressed in both psoriatic skin lesions and psoriatic patient-derived NET-stimulated keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In excess, they can cause dysregulated inflammation and persistent mucosal injury as evidenced by inflammatory bowel disease [45] . They also constitute an important component of the immune interaction in a variety of solid tumors including breast [47] , gastric [48] , melanoma [49] , RCC [50] , and CRC [51] . A fair amount of literature supports the role for neutrophils both in circulation and within the TME as being associated with cancer progression and prognosis [51] , [52] , [53] .…”
Section: The Microbiome and Innate Immune Cells In The Tumor Microenv...mentioning
confidence: 99%